2020
DOI: 10.1002/agj2.20203
|View full text |Cite
|
Sign up to set email alerts
|

Defining optimal soybean seeding rates and associated risk across North America

Abstract: Soybean [Glycine max (L.) Merr.] seeding rate research across North America is typically conducted in small geo-political regions where environmental effects on the seeding rate × yield relationship are minimized. Data from 211 individual field studies (∼21,000 data points, 2007-2017) were combined from across North America ranging in yield from 1,000-7,500 kg ha −1 . Cluster analysis was used to stratify each individual field study into similar environmental (soil × climate) clusters and into high (HYL), medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 38 publications
(66 reference statements)
5
38
0
Order By: Relevance
“…It has been documented in North Carolina that producers are at maximum yield potential if they achieve final populations of 185,250 and 222,300 plants ha −1 in May and June planted soybean, respectively (Dunphy, 2017). A recent national analysis of 211 field sites suggested that lower soybean‐seeding rates could be used in higher‐yielding (5,125–5,165 kg ha −1 ) environments (Gaspar et al., 2020), as would typically be encountered in a SYC. The ability of the soybean plant to compensate for lower‐than‐historically used populations is likely a result of breeding efforts that have resulted in higher yield potential per plant (Suhre et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It has been documented in North Carolina that producers are at maximum yield potential if they achieve final populations of 185,250 and 222,300 plants ha −1 in May and June planted soybean, respectively (Dunphy, 2017). A recent national analysis of 211 field sites suggested that lower soybean‐seeding rates could be used in higher‐yielding (5,125–5,165 kg ha −1 ) environments (Gaspar et al., 2020), as would typically be encountered in a SYC. The ability of the soybean plant to compensate for lower‐than‐historically used populations is likely a result of breeding efforts that have resulted in higher yield potential per plant (Suhre et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In Wisconsin, seeding rates between 296,400 and 345,800 seeds ha −1 yielded similarly (Gaspar et al., 2015). In a regional study, the AOSR for the Midwest was 365,000 seeds ha −1 (Gaspar et al., 2020). The seeding rate value selected in the CI tree analysis is likely near or in excess of the AOSR for each TED given past seeding rate studies, so the lower yield in fields with higher seeding rates in TEDs 7, 8, and 10 was likely due at least in part to high seeding rate and not just an artifact of farmers selecting higher seeding rates for fields with lower yield potential.…”
Section: Discussionmentioning
confidence: 99%
“…A seeding rate of 531,050 seeds ha −1 was used targeting an established plant population of 454,000 plants ha −1 based on 95% germination and about 10% expected seed to established plant loss [17]. However, the actual achieved plant population was on average about 300,000 plants ha −1 , still well within in the normal range for the Northern soybean region [18].…”
Section: Treatmentsmentioning
confidence: 99%